0.5T MRI as a competitor to CT for sinus imaging - Mark Parker; Steven Beyea; James Rioux; Brian King; Mohamed Abdolell; Sarah Reeve; Beverly Lieuwen; Chris Bowen; David Volders (Scientific Reports)
Abstract The goal of this study was to determine how radiologists’ rating of image quality when using 0.5T Magnetic Resonance Imaging (MRI) compares to Computed Tomography (CT) for visualization of pathology and evaluation of specific anatomic regions within the paranasal sinuses. 42 patients with clinical CT scans opted to have a 0.5T MRI scan for this study. Scans were completed from June 2021 to June 2022 with an average of 65.2 days from CT to MRI. A neuroradiologist and neuroradiology fellow evaluated the images to answer several questions and provide a confidence score for each based on image quality. Responses between the CT and MRI scans were compared for intramodality and intermodality agreement. The Likert scores demonstrate that MRI performed well in assessing mucosal thickening. Performance was not adequate for anatomical questions for presurgical planning. 0.5T MRI is able to produce high quality imaging of the sinuses. This could be used as a radiation free test to correlate mucosal thickening with patient’s symptoms. However, a CT would be needed to screen for ostiomeatal obstruction and anatomical visualization of critical variants for presurgical planning.